Inactive lifestyles and sedentary behavior in persons with chronic aneurysmal subarachnoid hemorrhage: evidence from accelerometer-based activity monitoring. Issue 1 (December 2017) - Harmsen, Wouter; Ribbers, Gerard; Heijenbrok-Kal, Majanka; Bussmann, Johannes; Sneekes, Emiel; Khajeh, Ladbon; van Kooten, Fop; Neggers, Sebastian; van den Berg-Emons, Rita
Abstract Background Aneurysmal subarachnoid hemorrhage (a-SAH) is a potential life-threatening stroke. Because survivors may be at increased risk for inactive and sedentary lifestyles, this study evaluates physical activity (PA) and sedentary behavior (SB) in the chronic phase after a-SAH. Methods PA and SB were objectively measured at six months post a-SAH with an accelerometer-based activity monitor, with the aim to cover three consecutive weekdays. Total time spent in PA (comprising walking, cycling, running and non-cyclic movement) and SB (comprising sitting and lying) was determined. Also, in-depth analyses were performed to determine the accumulation and distribution of PA and SB throughout the day. Binary time series were created to determine the mean bout length and the fragmentation index. Measures of PA and SB in persons with a-SAH were compared to those in sex- and age-matched healthy controls. Results The 51 participants comprised 33 persons with a-SAH and 18 controls. None of the participants had signs of paresis or spasticity. Persons with a-SAH spent 105 min/24 h being physically active, which was 35 min/24 h less than healthy controls (p = 0.005). For PA, compared with healthy controls, the mean bout length was shorter in those with a-SAH (12.0 vs. 13.5 s, p = 0.006) and the fragmentation index was higher (0.053 vs. 0.041, p < 0.001). Total sedentary time during waking hours showed no significant difference between groups (514 min vs. 474 min, p = 0.291). For SB, the mean bout length was longer in persons with a-SAH (122.3 vs. 80.5 s, p = 0.024), whereas there was no difference in fragmentation index between groups (0.0032 vs 0.0036, p = 0.396). Conclusions Persons with a-SAH are less physically active, they break PA time into shorter periods, and SB periods last longer compared to healthy controls. Since inactive lifestyles and prolonged uninterrupted periods of SB are independent risk factors for poor cardiovascular health, interventions seem necessary and should target both PA and SB. Study registration Dutch registry number: NTR 2085.